Measurement of vitamin D in dried blood spots stored under different temperature conditions. (September 2021) - Nybo, Mads; Fruekilde, Palle N; Andersen-Ranberg, Karen
Background: As part of the Survey of Health, Ageing and Retirement in Europe (SHARE) study, dried blood spot samples were obtained for measurement of potential biological biomarkers, among those vitamin D. Unfortunately, no studies describe the impact of high temperatures on dried blood spot samples and vitamin D measurements. Materials and methods: Capillary samples were collected on dried blood spot cards from 40 outpatients (median age 78 years) along with venous blood samples. To mimic the different environmental and temporal challenges during collection and shipment until final storage in the SHARE study, dried blood spot cards were stored at different temperatures, at time span and with/without freeze-thaw. Vitamin D concentrations in venous plasma samples were measured by conventional immunoassay (on Architect i2000SR), while vitamin D concentrations in dried blood spot samples were measured using LC-MS/MS with a well-described extraction method and with relevant calibration and comparison with a reference method. Results: Vitamin D measured in dried blood spot samples did not differ significantly from venous plasma measurements under the different storage conditions tested. The optimal vitamin D correlation between the two matrices was by storage at either 21°C or 35°C for four days (r = 0.9060 and 0.9026, respectively). Freeze-thaw of the dried blood spot samples did not have any significant effect. Conclusion: We find that vitamin D measured in dried blood spot samples do not differ significantly from venous plasma measurements despite storage at different temperatures and freeze-thaw, which enables the use of dried blood spot in multicentre studies taking place under alternating temperature conditions.